Incidence, clinical features, laboratory findings and outcome of patients with multiple myeloma presenting with extramedullary relapse. Issue 7 (1st July 2013) - Papanikolaou, Xenofon; Repousis, Panagiotis; Tzenou, Tatiana; Maltezas, Dimitris; Kotsopoulou, Maria; Megalakaki, Katerina; Angelopoulou, Maria; Dimitrakoloulou, Elektra; Koulieris, Efstathios; Bartzis, Vassiliki; Pangalis, Gerasimos; Panayotidis, Panagiotis; et al.
Abstract: Extramedullary plasmacytomas constitute a rare and not well studied subset of multiple myeloma (MM) relapses. We report the incidence, clinical–laboratory features and outcome of patients with MM and extramedullary relapse (ExMeR). A total of 303 patients with symptomatic MM were recorded in a 13-year period in two institutions. Twenty-eight cases of ExMeR (9%) were recorded. There was an increased frequency of elevated lactate dehydrogenase (LDH) ( p = 0.026), bone plasmacytomas ( p = 0.001) and fractures ( p = 0.002) at diagnosis, in patients with ExMeR compared to the others. ExMeR was associated with an ominous outcome, high LDH, constitutional symptoms and a statistically significant decrease of monoclonal paraprotein compared to levels at diagnosis ( p = 0.009). Prior treatment with bortezomib was associated with a decreased hazard of ExMeR ( p = 0.041). Overall survival (OS) was decreased in patients with ExMeR compared to the others (38 vs. 59 months, p = 0.006). Patients with MM with ExMeR have a lower OS and their clinical and laboratory features differ from those without.